2006
DOI: 10.1007/s11655-006-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astragalus membranaceus in promoting T-helper cell type 1 polarization and interferon-γ production by up-regulating T-bet expression in patients with asthma

Abstract: AM could increase the expression of T-bet mRNA and Thl cytokines such as IFN-Y, and might reverse the Th2 predominant status in asthma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Higher levels of IL-1, IL-6, IL-8, and TNF␣ were found in children with nephrotic syndrome when treated with A. membranaceus (Peng et al 2005). In asthmatic patients treated with A. membranaceus, the mRNA expression of the Th1 transcription factor T box in T cells was significantly increased and the level of IL-4 was decreased (Wang et al 2006). Although controversial results exist regarding the treatment of allergic patients with A. membranaceus, most reports favor its Th1-polarizing effect on asthma, cancer, herpes simplex keratitis, or type I diabetes (Tomas 2011).…”
Section: Fig 2 Effects Of a Membranaceus On The Antibody Levels Ofmentioning
confidence: 99%
“…Higher levels of IL-1, IL-6, IL-8, and TNF␣ were found in children with nephrotic syndrome when treated with A. membranaceus (Peng et al 2005). In asthmatic patients treated with A. membranaceus, the mRNA expression of the Th1 transcription factor T box in T cells was significantly increased and the level of IL-4 was decreased (Wang et al 2006). Although controversial results exist regarding the treatment of allergic patients with A. membranaceus, most reports favor its Th1-polarizing effect on asthma, cancer, herpes simplex keratitis, or type I diabetes (Tomas 2011).…”
Section: Fig 2 Effects Of a Membranaceus On The Antibody Levels Ofmentioning
confidence: 99%
“…Many studies have found that AM has the obvious therapeutic effect on allergic diseases, such as asthma and AR. 2022 Due to its complex therapeutic mechanism, extensive studies and reports are still lacking. Therefore, we mainly studied the role of AM in the mouse model of AR.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, Yang et al reported AM raising the immune response of the host organism to against tumor activity of liver cancer. 19 Beyond that, although AM has long been used in the treatment of asthma and AR, 20,21 the mechanism for treating AR remains unclear. Therefore, we hereby investigate the anti-inflammatory effect of AM and whether this effect is associated with the CD4 þ CD25 þ Foxp3 þ T cells and NF-jB pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Der Bestandteil Astragalus (Huang qi) zeigte auch eine IFN-γ-aktivierende sowie eine IL-4-hemmende Wirkung bei Asthmatikern und könnte daher zu einer Verbesserung der Dysregulation der Th1/Th2-Balance bei Asthmatikern beitragen (Wang et al 2006).…”
Section: Anmerkung Der Autorinunclassified